An Inefficacious Shock Therapy?: A Critical Analysis of Mongolian Neoliberal Reforms (Mongolian Journal of International Affairs, 2022)
This research aims to critically review the development process and connotation of neoliberal reform in Mongolia, which has been implemented since 1991 under the International Monetary Fund’s (IMF) program. This paper outlines the historical context of the transition, the so-called shock therapy, and analyzes Mongolia’s economic performance and socioeconomic changes after neoliberal reform, particularly focusing on the free market monetary policy. The policy was a crucial turning point for Mongolia, in which neoliberalism almost eliminated the former socialist planned economy and took a dominant position in the Mongolian political economy. Over the past three decades, successive administrations have implemented various measures based on a free monetary policy promoted by the IMF to obtain foreign loans and aid. However, despite the long-term reforms, thorny issues, such as a sharp currency depreciation, soaring debts, unemployment, inflation, budget deficits, poverty, crime, and corruption, still remain unresolved. In short, Mongolia’s shock therapy transition appears to be inefficacious. The nation may need to develop policies that take into account the characteristics of their economy and are able to stabilize people’s livelihoods.